The universal tree of life: an update - Forterre, Patrick (Frontiers in Microbiology, 2015)
Biologists used to draw schematic “universal” trees of life as metaphors illustrating the history of life. It is indeed a priori possible to construct an organismal tree connecting the three major domains of ribosome encoding organisms: Archaea, Bacteria and Eukarya, since they originated by cell division from LUCA. Several universal trees based on ribosomal RNA sequence comparisons proposed at the end of the last century are still widely used, although some of their main features have been challenged by subsequent analyses. Several authors have proposed to replace the traditional universal tree with a ring of life, whereas others have proposed more recently to include viruses as new domains. These proposals are misleading, suggesting that endosymbiosis can modify the shape of a tree or that viruses originated from the Last Universal Common ancestor (LUCA). I propose here an update version of the Carl Woese universal tree that includes several rooting for each domain and internal branching within domains that are supported by recent phylogenomic analyses of domain specific proteins. The tree is rooted between Bacteria and Arkarya, a new name proposed for the clade grouping Archaea and Eukarya. A consensus version, in which each of the three domains are unrooted, and a version in which eukaryotes emerged within archaea are also presented. This last scenario assumes the transformation of a modern domain into another, a controversial evolutionary pathway. Viruses are not indicated in these trees but are intrinsically present because they infect the tree from its roots to its leaves. Finally, I present a detailed tree of the domain Archaea, proposing the sub-phylum neo-euryarchaeota for the monophyletic group of euryarchaea containing DNA gyrase. These trees, that will be easily updated as new data become available, could be useful to discuss controversial scenarios regarding early life evolution.